TREND ANALYSIS OF UGANDA’S COFFEE SECTOR - ATEGEKA, STEWART (Applied Studies in Agribusiness and Commerce, 2023)
Coffee (Coffea arabica and C. canephora) is an important commercial crop globally, and the second most traded global commodity by developing nations after oil. Uganda is among the top 10 coffee exporters worldwide, and second in Africa. The total export amounted to 301,366 tons of “green” coffee in 2021, forming the second-largest commodity export, and contributing about 12.4% to Uganda’s total formal exports. However, the country’s overall performance over time remains unclear given the fluctuations in production and export prices.   This study aimed to evaluate the production and export trends of Uganda’s coffee sector by: (i) defining the overall direction of coffee production and export value, (ii) assessing the market variability, and (iii) evaluating the global cross-cutting issues regarding coffee production and export. Data was extracted from FAOSTAT and Uganda Coffee Development Authority (UCDA) databases. Trends were analysed using the Mann-Kendall and Sen’s Slope test, while market variability was analyzed using the fixed base index (FBI) and coefficient of variation. VOSviewer software was used to analyze literature from the Web of Science database to highlight cross-cutting issues. Results indicated a significant positive increase in coffee production and export value (p = 0.0001, Slope = 1736.67 tons and p = 0.001, Slope = 4.44 million USD) respectively. Among the top ten coffee producers, Uganda presented the third worst unstable coffee export value with a 20.1% coefficient of variation. Fairtrade, climate change, and certification were the most outstanding global cross-cutting issues. Market stabilization mechanisms should be developed through value addition by establishing coffee processing and roasting plants, as well as strategic governance and policy support to counter emerging global challenges such as climate change.